Una revisión crítica para la construcción de indicadores sintéticos - Mónica Domínguez Serrano; Francisco Javier Blancas Peral; Flor María Guerrero Casas; Mercedes González Lozano (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2011)
– This paper presents a critical analysis of some of the techniques which are applied in practice to obtain composite indicators from a previous sub-indicator system. In studying each methodology, we identify the advantages and disadvantages associated with them, paying particular attention to issues such as reducing the subjectivity associated with synthetic indicator, the ease of interpretation of results, operational complexity, etc. Therefore, we offer a document that can be used by analysts to choose the methodology that best suits their studies.
Keywords: C61; C1; C43; 330; composite indicator; aggregation methodologies; multivariate analysis; multicriteria analysis